Pelatihan Pembuatan Program Outbound Tim Building Bagi Guru MGMP PJOK Tingkat SD Se-Kota Kupang - Siagian, Fera Ratna Dewi; Boleng, Lukas Maria; Babang, Veramyta Maria Martha Flora; Ladjar, Maria Andriani Barek; Siahaan, Jurdan Martin (Universitas Nusa Cendana, 2024)
Team collaboration, commonly known as team building, is an essential aspect in the era of Society 5.0. Through collaboration, team members can create effective communication and cooperation. One way to train team building is through outbound programs. However, outbound programs are still not well known among PE teachers. Therefore, through this community service activity, the community service team offers a solution to introduce outbound programs while providing a means for teachers to develop their innovation and creativity. The program is titled